2009
DOI: 10.1007/s00535-009-0033-y
|View full text |Cite
|
Sign up to set email alerts
|

Intra-arterial 5-fluorouracil/interferon combination therapy for advanced hepatocellular carcinoma with or without three-dimensional conformal radiotherapy for portal vein tumor thrombosis

Abstract: 5-FU/IFN combination with 3D-CRT for PVTT improved the response rate of PVTT and reduced the incidence of portal hypertension-related events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 42 publications
2
61
3
Order By: Relevance
“…Several previous publications have reported outcomes of PVTT treated with or without 3D-CRT [39,40,41,42,43,44]. Table 2 summarizes the clinical results after EBRT for treatment of PVTT only with or without other treatments.…”
Section: Role Of Radiation Therapy: Clinical Outcomes Of 3d-crt For Tmentioning
confidence: 99%
See 2 more Smart Citations
“…Several previous publications have reported outcomes of PVTT treated with or without 3D-CRT [39,40,41,42,43,44]. Table 2 summarizes the clinical results after EBRT for treatment of PVTT only with or without other treatments.…”
Section: Role Of Radiation Therapy: Clinical Outcomes Of 3d-crt For Tmentioning
confidence: 99%
“…Yamada et al []42] studied the use of an anteroposterior parallel opposing field treatment design and reported an increased risk of gastroduodenal ulceration or bleeding. Severe hematologic toxicity associated with the use of high dose intra-arterial chemotherapeutic agents [39] and transient liver enzyme elevations were also reported. Kim et al []36] reported that in most cases of liver enzyme elevation, the levels were less than five-fold the upper normal limit and the elevation was usually self-limited.…”
Section: Efficacy and Toxicity Of Pvtt Treatment With Radiation Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Although HAI was not statistically beneficial in our study, selection bias occurred as we already mentioned. RT combined with HAI was tried by some authors (22,23) and yielded some therapeutic efficacy. Han et al (23) performed concurrent treatment of RT and HAI in 40 HCC patients with PVT, and showed a favourable result (median survival, 13.1 months.).…”
Section: Jpn J Clin Oncol 2012;42(8) 727mentioning
confidence: 99%
“…Among several anticancer agents, intra-arterial 5-FU and systemic IFN-α were reported as one of the effective combination chemotherapies for HCC with portal vein tumor thrombosis (PVTT) [7,9,12,13]. Furthermore, the efficacy of combination therapy of HAIC and three-dimensional (3D) conformal RT (3D-CRT) for PVTT has been reported as an MST of 13.1 months in HCC patients with PVTT treated by HAIC + RT [10,14].…”
Section: Introductionmentioning
confidence: 99%